The Nagorno-Karabagh Conflict from the Perspective of Western Media: Reason,Type, Provocateur and Victim ﻿ - Aghayev, Orkhan (My University, 2016)
This paper analyzes the Western Media coverage of the Armenia-Azerbaijan conflict over the Nagorno-Karabakh region by applying content analysis. The primary aim of this research is to find out the reasons, type, provocateur and victim of this conflict from the perspective of the Western media as well as the factors that may have resulted in changes in the Western Media coverage of this conflict. The importance of this research stems from many factors. One of these factors is the Media's ability to shape people's minds as well as to influence governments' decisions about a particular issue, which is why it is usually called the fourth estate 1• I will broadly cover the aspects that make this research important in introduction. Besides this the research design, preliminary analysis as well as limitations of the research will be explained in introduction. The second part will examine the Western media reporting as a whole, while the thir, fourth and fifth parts of the research will three different newspapers chosen to represent the Western Media (more precisely, the New York Times, the Independent and Der Spiegel) separately from one another and the sixth part will compare their differences from each other. The last part of the paper will serve as a conclusion to sum up the results gained from the analysis.
Keywords: Public and International Affairs; Nagorno-Karabakh Conflict, 1988-1994; Nagorno-Karabakh Conflict, 1988-1994 -- History; Nagorno-Karabakh Conflict, 1988-1994 -- Western media; Azerbaijan -- Relations -- Armenia (Republic); Armenia (Republic) -- Relations -- Azerbaijan